What factors affect a patient's subjective perception of MRI examination - Dostál, Marek; Jurasová, Kateřina; Keřkovský, Miloš; Vaníček, Jiří; Kalas, Ladislav; Látal, Luboš; Janků, Svatava; Trojek, Vladimír; Šprláková-Puková, Andrea (Scientific reports, 2024)
MRI is becoming increasingly available and more common. However, it is a long examination, within a limited space, and making strong demands on the patient for proper co-operation. Using survey data collected by prospective questionnaire, this work examines the influence of patient preparation and type of MRI device on patients' subjective perception of the examination. The work analysed 800 patient questionnaires from 7 radiology centres, 12 MRI machines from 3 manufacturers. It was shown that 20% of patients were not informed at all or only insufficiently about the MRI examination by the referring physician, and this had a statistically significant effect on subjective perception as to the length of the examination. In claustrophobic patients, there was no significant difference in the perception of MRI examination between machine types (open vs. closed) or between bore size. This work demonstrated the influence of technical parameters of MRI devices on some other evaluated aspects in terms of patients' perception of MRI examinations (such as noise perception or peripheral nerves irritation) and that the preparation prior to the examination itself plays also an important role. Sufficient explanation from the referring physician, good workplace time management, and sufficient communication with the patient influence the subjective perception of the examination and thus indirectly its diagnostic benefit.
Keywords: senioři; mladiství; Middle Aged; průzkumy a dotazníky; percepce; mužské pohlaví; Prospective Studies; Adult; mladý dospělý; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Young Adult; ženské pohlaví; Humans; prospektivní studie; Surveys and Questionnaires; lidé středního věku; Perception; dospělí; Female; Aged; Adolescent; lidé; Male